INTERNALISASI NILAI PENDIDIKAN AGAMA ISLAM DALAM PROGRAM UNGGULAN MOSA PATRI RELIGI GO TO IMAN DI SDN MOJOREJO 1 KOTA BATU - Khisma Maula Umadatul Aziroh; Mohammad Samsul Ulum; Mokhammad Yahya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the process of internalizing the values of Islamic Religious Education (PAI) in the flagship program MOSA Patri Religi Go to IMAN at SDN Mojorejo 1 Kota Batu. This program is developed as an effort to strengthen the character of students through five main pillars, namely patriotism, religiosity, mutual cooperation, integrity, and independence, which are aligned with the Pancasila Student Profile. The research uses a qualitative approach with a case study design. Data were obtained through observation, in-depth interviews with the school principal, PAI teachers, program coordinators, and documentation of various school activities. The research results show that the internalization of PAI values occurs through three stages: value transformation, value transaction, and transinternalization. In the value transformation stage, teachers introduce values through learning and exemplary behavior. In the value transaction stage, students actively participate in activities such as congregational prayer, PAP, flag ceremonies, class duties, community service, and scouting. Meanwhile, in the transinternalization stage, these values are reflected in daily behaviors such as independence, discipline, social concern, honesty, and religious attitudes that emerge spontaneously. This program has proven to have a positive impact on strengthening the aspects of faith, worship, and morals of students, as well as forming a strong social-national character. Program evaluation is conducted periodically through observation of student behavior, attitude assessment, and communication with parents. Overall, the MOSA Patri Religi Go to IMAN program is effective as a holistic model for cultivating PAI values and has the potential to be replicated by other schools.